The Electric Vehicle Bi-directional DC/DC Converter Base on Fuzzy PI Control - DING Xiying; YU Hua; LI Jian; ZHANG Qinshuang (Kongzhi Yu Xinxi Jishu)
The particularity of electric vehicles DC power source and high quality requirement determine that DC /DC converter requires stable voltage and current output. To solve the serious nonlinear problem in process of vehicle’s status switching, chop-control is adopted which is composed by conventional PI control in current loop and fuzzy PI control voltage loop. In the analysis of bi-directional DC / DC converter working principle, the fuzzy PI controller is designed based on the change of its own structural characteristics of the converter. The simulation results show that the control scheme effectively improves the robustness of the converter and reduces the output voltage fluctuations.